Competencies management functions and their impact on improving job performance A field study of a sample of institutions in Tlemcen. - Khaled Fettouh (Dirassat Journal Economic Issue, 2022)
This study aims to identify the extent of the impact of competency management functions in improving job performance, and to highlight this, we conducted a field study of a sample of institutions (Directorate of Water resources, Algérian Water, Sonlegaz) in Tlemcen, consisting of 102 questionnaires.Where the (spss) program was used in statistical processing and data analysis, and in order to test the hypotheses, the simple and multiple linear regression method was used. The study concluded that there is no statistically significant effect (for the recruitment of competencies, evaluation of competencies) on job performance, in contrast there is a statistically significant effect (for the developing of competencies, wages and incentives for competencies) on job performance.